Effects of Air Pollutants on the Composition of Stable Carbon Isotopes, δ(13)C, of Leaves and Wood, and on Leaf Injury - Martin, Bjorn (1988)
Air pollutants are known to cause visible leaf injury as well as impairment of photosynthetic CO(2) fixation. Here we evaluate whether the effects on photosynthesis are large enough to cause changes in the relative composition of stable carbon isotopes, δ(13)C, of plant tissue samples, and, if so, how the changes relate to visual leaf injury. For that purpose, several woody and herbaceous plant species were exposed to SO(2) + O(3) and SO(2) + O(3) + NO(2) for one month (8 hours per day, 5 days per week). At the end of the fumigations, the plants were evaluated for visual leaf lesions, and δ(13)C of leaf tissue was determined. Woody plants generally showed less visual leaf injury and smaller effects on δ(13)C of pollutant exposure than did herbaceous plants. If δ(13)C was affected by pollutants, it became, with few exceptions, less negative. The data from the fumigation experiments were consistent with δ(13)C analyses of whole wood of annual growth rings from two conifer tree species, Pseudotsuga menziesii and Pinus strobus. These trees had been exposed until 1977 to exhaust gases from a gas plant at Lacq, France. Wood of both conifer species formed in the polluted air of 1972 to 1976 had less negative δ(13)C values than had wood formed in the much cleaner air in 1982 to 1986. No similar, time-dependent differences in δ(13)C of wood were observed in trees which had been continuously growing in clean air. Our δ(13)C data from both relatively short-term artificial exposures and long-term natural exposure are consistent with greater stomatal limitation of photosynthesis in polluted air than in clean air.